History of Educational and Scientific Works in Andijan State Medical Institute - Toshpulatov Bekzod Shuxratovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article is devoted to the study of the history of the formation of the system of higher medical education in the Andijan region and the stages of its development. The Andijan Medical Institute and its importance in the training of medical personnel in the region are analyzed.